1979
DOI: 10.1021/ac50045a015
|View full text |Cite
|
Sign up to set email alerts
|

Comparative interference study for atomic absorption lead determinations using a constant temperature vs. a pulsed-type atomizer

Abstract: It is anticipated that high precision analyses via the ICP can be expanded to a wide range of elements and can be applied to a large variety of samples which are currently analyzed by other methods.During the one to three seconds necessary to heat commercial electrothermal atomizers to the desired atomization temperature, many reactions take place, and analyte compounds may be lost from the rapidly heating furnace at varying temperatures with varying matrices-often at sub-optimal temperatures with inadequate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 52 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…With the FASTAC/ microboat combination, however, the measured results for both methods were close to the NBS reported results. CONCLUSION Previous workers have convincingly shown that some interferences with Massmann-style furnace AA results because atomization occurs while the temperature of the cuvette is changing rapidly and the temperature of the gas-phase environment kgs behind the temperature of the graphite surface (1)(2)(3)(4)(5)(6)(7)(8). Atomization into a cooler temperature environment makes the analytical results highly dependent on the matrix of the sample.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…With the FASTAC/ microboat combination, however, the measured results for both methods were close to the NBS reported results. CONCLUSION Previous workers have convincingly shown that some interferences with Massmann-style furnace AA results because atomization occurs while the temperature of the cuvette is changing rapidly and the temperature of the gas-phase environment kgs behind the temperature of the graphite surface (1)(2)(3)(4)(5)(6)(7)(8). Atomization into a cooler temperature environment makes the analytical results highly dependent on the matrix of the sample.…”
Section: Resultsmentioning
confidence: 92%
“…Numerous researchers have reported on analytical systems which reduce matrix interferences commonly experienced in furnace atomizer atomic absorption spectrometry. Woodriff et al (1) reported that their constant temperature furnace was free from some matrix interferences commonly experienced with pulsed-type furnace atomizers. In 1977, L'vov (2) suggested that the placement of a graphite platform within a cylindrical pulsed-type furnace should approximate a constant temperature design.…”
mentioning
confidence: 99%
“…When the furnace is operated at a steady-state temperature (2,3,(5)(6)(7)(8)(9) during the time the analyte is vaporized and the absorbance signal is integrated, many of the interferences previously reported for graphite furnace analyses have been reduced or eliminated. Larger amounts of sample can be analyzed if Zeeman background correction is used (4).…”
mentioning
confidence: 99%
“…Variations in the first two parameters do not affect the integrated absorbance signal if the sample is vaporized into a constant temperature environment (1). Gas-phase interferences can be substantially reduced or eliminated (depending on the matrix concentration) provided the temperature and residence time are both sufficiently large (2). Some recent work with pulse-type furnaces has therefore been aimed at delaying sample vaporization until the entire furnace is at least equal to or greater than the appearance temperature of the element of interest (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…The solution dries on contact leaving a uniform layer of fine crystals. The authors propose that this method of sample deposition overcomes sources of interference due to (1) matrix-dependent spreading of the sample droplet, (2) variable seepage of the solution into the graphite layers, and (3) formation of large crystals which can trap the analyte and be expelled from the furnace before decomposing. Definitely, more work needs to be done on this system to clearly elucidate the mechanism of the improvements.…”
mentioning
confidence: 99%